2006
DOI: 10.1159/000096968
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development in a Heliox Incubator Environment: A Long-Term Safety Study

Abstract: Background: Neonates exposed to mechanical ventilation may develop bronchopulmonary dysplasia (BPD). BPD neonates exhibit a 25–30% increase in energy expenditure which may decrease the rate of growth and development. Heliox has been shown to improve pulmonary function and may decrease energy expenditure. We hypothesized that heliox would provide a safe environment for sustained growth and development. Objective: To assess the safety of the heliox environment we observed developmental milestones; recorded chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The effect of 14 days in a heliox (21% oxygen, 79% helium) environment has been tested in 4-day-old rabbit kits. No differences in weight, growth factors, tissue/organ weights, blood chemistries, or muscle enzyme activity were detected between heliox-and air-exposed animals (106). This finding has relevance for human infants treated with heliox to decrease gas viscosity in obstructive lung conditions.…”
Section: Other Newborn Rabbit Modelsmentioning
confidence: 63%
“…The effect of 14 days in a heliox (21% oxygen, 79% helium) environment has been tested in 4-day-old rabbit kits. No differences in weight, growth factors, tissue/organ weights, blood chemistries, or muscle enzyme activity were detected between heliox-and air-exposed animals (106). This finding has relevance for human infants treated with heliox to decrease gas viscosity in obstructive lung conditions.…”
Section: Other Newborn Rabbit Modelsmentioning
confidence: 63%
“…It was also observed that long-term exposure to heliox caused no long-term differences in growth or development in newborn rabbits [18] . Poor heliox tolerance (hypoxia, decrease in skin temperature, wakening and crying) was described in spontaneously breathing infants with BPD when heliox was administered into a plexiglass chamber [19] .…”
Section: Discussionmentioning
confidence: 95%
“…These benefits of HFNC are amplified with the use of Heliox, since it is unique biophysical properties aid in improving work of breathing, improves ventilation, decreases oxygen needs, may enhance nasopharyngeal washout (more effective diffusion of Heliox), and further reduces lung inflammation . In addition, Heliox provides an effective steady state thermal environment during early development …”
Section: Discussionmentioning
confidence: 99%